Investigations on alloxan-lnduced diabetes in the dogs - Ali Muhtar Tiftik; Kürşat Turgut; Mehmet Gürbilek; Mutlu Sevinç (Eurasian Journal of Veterinary Sciences)
In this investigation, nine healthy dogs weighing from 9 to 20 kg were used. The dogs were made diabetic by a single intravenous injection of 0.60-0.70 mmol/kgbw of alloxan, intravenous glucose tolerance tests (IVGTT) were done at the beginning of the study and in the second weeks of alloxan injections. At the beginning of the study, the mean values of fasted plasma glucose and insulin were found to be 4.56 ± 0.32 mmol/1 and 9.73 ±2.69 m U/ml respectively. After the alloxan injections, clear hyperglycemia and decreasing insulin levels were determined and plasma insulin levels waried between 0-5.33 m U/ml during the study. In the urinalyses, glucosuria, ketonuria, proteinuria and decreased urinary pH levels were observed in the alloxan diabetic dogs. After diabetes occured, experimental diets (low high fibre diets) periode was started. Jncreasig plasma glucose levels were determined During the low fibre diet periode whereas decreasing glucose levels determined in the high diet periode. It is concluded that, it is necessary to apply the IVGTT for the certain diagnosis of diabetes and it is appropriate the recommend of rye bread for the regulation of hyperglycemia.